Role of Panchkarma in Public Health Scenario -A Conceptual Study - Puri, Snehal Ganeshrao; Dhaked, Pradeep; Rajpurohit, Kripal Singh; Jangid, Jyoti (International Research Journal of Ayurveda & Yoga, 2023)
Background: "Health" is a condition of complete physical, mental, and social well-being, not just the absence of sickness or disability." Panchakarma is used to eliminate toxins from the body and keep the digestive fire burning. It’s a considered trying natural therapy for re-igniting the digestive fire and, as a result, restoring the body’s balance and vigour. The Panchakarma method involves returning accumulated toxins to the GI tract and removing these toxins from the nearest root. Panchakarma is a Penta bio purification procedure that helps to restore body humour balance, eliminate disease-causing complexes from the body, and prevent disease recurrence and development. People’s health concerns can be satisfactorily resolved if Panchakarma is well supported by scientific documentation and confirmation. Aims and Objectives: The major goal of Panchkarma procedure is to maintain healthy people well and to cure diseased people. Material and methods: Classical treatises of Ayurveda along with modern standard textbooks related with Panchkarma were scrutinized. Conclusion: Panchakarma procedures assist Shodhana in detoxifying such toxins and balancing the Doshas, preventing disease, improving people’s lives, and making it possible to achieve public health.